Customer Perceived Value- Challenges and Opportunities of Indian Retail Stores - Gupta, Archit (2016)
Over the period of time, the significance of shopping has transformed for the customers. It was just a requirement for them initially. Shopping and retailing was used to be a very easy concept in India, buying the products required from the traditional local stores from the nearest place. The change has brought up by the western companies. The factors that influenced the store choice have also changed. The customers are not just looking for the products, but also attracts from space, convenience and ambience and furthermore large variety of products under one roof. Shopping is not merely a necessity now. These factors are beginning to play avital role in magnetizingthe potential customers. Many huge international companies like Wal-Mart have penetrated the Indian market and are trying to steal the customers from the traditional unorganized market. There is definitely a lot of growth in the organized sector and the unorganized sector needs to cope up with the latest trends of the market.